Laser diodes employing GaAs1−xBix/GaAs1−yPy quantum well active regions. (27th June 2017) - Kim, Honghyuk; Guan, Yingxin; Forghani, Kamran; Kuech, Thomas F; Mawst, Luke J
Abstract: Laser diodes employing strain-compensated GaAs1− x Bi x /GaAs1− y P y quantum well (QW) active regions were grown by metalorganic vapor phase epitaxy (MOVPE). High resolution x-ray diffraction, room temperature photoluminescence, and in situ optical reflectance monitoring during the MOVPE growth provided valuable feedback for the optimization of the material growth conditions. In addition, the post-growth in situ thermal annealing was employed to improve the radiative efficiency of the GaAs1− x Bi x /GaAs1− y P y QW structures. Wide ridge waveguide lasers with GaAs barriers exhibited high threshold current densities ( J th  ∼ 8 kA cm −2 ), excessive band-filling, and carrier leakage at room temperature, resulting in the lasing from a high energy transition. By contrast, devices employing GaAs1− y P y barriers exhibited significantly lower threshold current densities ( J th  ∼ 5.9 kA cm −2 ), and longer wavelength QW emission, presumably as a result of improved active region carrier confinement. Devices with GaAs0.8 P0.2 barriers after the post-growth thermal annealing exhibited further reduced threshold current density ( J th  ∼ 4.1 kA cm −2 ).